اختبار بعض محددات الأداء المالي لشركات التأمين السورية للسنوات من 2008-2019: دراسة تحليلية قياسية - نمير امير جاسم الصائغ; زينب مصعب عبدالسلام (PROSPECTIVE RESEARCHES, 2023)
The research seeks attempt to diagnose the most important factors affecting the performance of insurance companies as one of the most important parts of the financial system, which is affected by many internal variables extracted from the statement of financial position (balance sheet), income statement, cash flows statement or combining its parts such as the tangibility of assets, financing composition, trading ratios, and previous profit growth This is done by selecting and filtering the data and selecting the most appropriate ones for econometric model, and with three main models, the first of which came with the return on assets, the second with the return on the stock and the last with the market value. Total assets were among the most influential independent variables, followed by the current ratio and short-term financing to total financing, and based on the conclusions, some proposals were reached, perhaps the most important of which is that the financial managers of such firms should interact more with the internal indicators that are reflected in the reports and financial statements, even if they Fall within the long-term or capital intensity of the large possibility The future performance is affected by it in the short or long term.